Economics: A Moral Inquiry with Religious Origins - Friedman, Benjamin M (American Economic Review, 2011)
In contrast to the standard interpretation of the origins of economics out of the secular European Enlightenment of the 18th century, the transition in thinking that we rightly identify with Adam Smith and his contemporaries and followers, which gave us economics as we now know it, was powerfully influenced by then-controversial changes in religious belief in the English-speaking Protestant world in which they lived: in particular, key aspects of the movement away from orthodox Calvinism. Further, those at-the-outset influences of religious thinking not only fostered the subsequent spread of Smithian thinking, especially in America, but shaped the course of its reception. The ultimate result was a variety of fundamental resonances between economic thinking and religious thinking that continue to influence our public discussion of economic issues, and our public debate over economic policy, today.